2009
DOI: 10.1037/a0014826
|View full text |Cite
|
Sign up to set email alerts
|

Non-suicidal self-injury and eating pathology in high school students.

Abstract: Although past research has explored self-injurious behaviors and disordered eating among adults in clinical settings, little research has been conducted examining nonsuicidal self-injury (NSSI) and eating pathology in community samples of adolescents. Four hundred and 40 students were screened for the presence of NSSI; a prevalence rate of 13.9% was found. Those who indicated that they engaged in NSSI (n = 59) and a comparison group of non-self-injurers (n = 57) completed the Eating Disorders Inventory. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
109
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(130 citation statements)
references
References 58 publications
14
109
1
6
Order By: Relevance
“…An emerging body of research has examined between-person factors that may explain the co-occurrence of NSSI and DE. Findings have implicated traits such as negative urgency (Claes et al, 2015a;Peterson and Fischer, 2012), emotion regulation difficulties (Muehlenkamp et al, 2012;Ross et al, 2009), problems in identity formation (Claes, et al, 2015b), mood and personality disorder symptoms (Yiu et al, 2014), and negative attitudes toward one's body (Muehlenkamp et al, 2011;Turner et al, 2015) in the co-occurrence of these two behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…An emerging body of research has examined between-person factors that may explain the co-occurrence of NSSI and DE. Findings have implicated traits such as negative urgency (Claes et al, 2015a;Peterson and Fischer, 2012), emotion regulation difficulties (Muehlenkamp et al, 2012;Ross et al, 2009), problems in identity formation (Claes, et al, 2015b), mood and personality disorder symptoms (Yiu et al, 2014), and negative attitudes toward one's body (Muehlenkamp et al, 2011;Turner et al, 2015) in the co-occurrence of these two behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Ross et al (2009) found a NSSI prevalence of 13.9% in students. Students engaging in NSSI compared to non-NSSI students completed the Eating Disorders Inventory: NSSI students showed significantly more eating pathology than their non-NSSI peers.…”
Section: Relationships Between Eds and Sibmentioning
confidence: 99%
“…Some patients with EDs use SIB to reduce distress and uncomfortable feelings Paul et al, 2002). Since the affective problems precede EDs and SIB, dysregulation of affect could be responsible for the onset of both pathologies, at least in some patients (Ross et al, 2009). …”
Section: Affect Dysregulationmentioning
confidence: 99%
See 2 more Smart Citations